Execution of Second-Rank Mortgage Rights Due to breach of contract at PT Bank Sulutgo - Rizky Fauzi R Zees; Djumikasih; Yeni Eta Widyanti (Institut Agama Islam Negeri Curup, 2025)
This study aims to analyze the effectiveness of Article 20, Paragraph (2) of Law Number 4 of 1996 on Mortgage Rights in the execution of mortgage guarantees due to Breach Of Contract, with a focus on the case of PT Bank Sulutgo. The main issue examined is the challenges in executing Second-Rank Mortgage Rights when multiple creditors are involved, as well as the legal uncertainty surrounding the private sale mechanism. This research employs an empirical juridical method with a socio-legal approach, combining document studies and interviews with relevant parties at PT Bank Sulutgo. The findings indicate that execution through public auction often encounters administrative and legal obstacles, particularly concerning the position of the Second-Rank Mortgage Rights holder, who is dependent on the First-Rank Mortgage Rights holder. Furthermore, the lack of clear regulations regarding the execution of Second-Rank Mortgage Rights leads to multiple interpretations in practice. As an alternative, private sales provide a more flexible solution; however, in the case of PT Bank Sulutgo, this mechanism negatively impacts other debtors who still have outstanding credit obligations. This study concludes that the effectiveness of Article 20, Paragraph (2) of the Mortgage Rights Law remains weak in providing legal certainty for Second-Rank Mortgage Rights holders. Therefore, more detailed regulations on the execution mechanism of Second-Rank Mortgage Rights are necessary to ensure legal protection for all parties involved.